Academism in the Assessments of Professors of Classical Universities - E. A. Popov (Высшее образование в России, 2022)
The article presents the results of an empirical study of academism in the assessments of professors of Russian classical universities. In total, 50 experts from various universities of Russia took part in the online survey. The aim of the study was to assess the role of academism in the development of university, maintaining the quality of education and maintaining the authority of professors at the university. The article gives a definition of the concept of academism, and reveals its structure. Basically, academism represents academic freedoms and the intellectual potential of the individual. The main results of the study include the following provisions: 1) academism is an integral part of a modern university and influences the formation of relevant values and traditions of university life; 2) academism influences the quality of students’ education, the preservation of high requirements in the educational process; 3) academism determines the authority of professors and teachers, promotes their active involvement in the social and cultural life of the university.